1999
DOI: 10.1046/j.1460-9568.1999.00469.x
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrophic factors modulate hair cells and their potassium currents in chick otocyst explants

Abstract: Neurotrophins, retinoids and their receptors are present in the sensory epithelia of the inner ear during development. We show that these factors modulate the proliferation of hair cells and their K+-currents when the embryonic day 3 (ED 3) presumptive inner ear (i.e. otocyst) is maintained in organ culture. All trans-retinoic acid (RA) increases hair cell differentiation and enhances the acquisition of outward currents, including a delayed rectifier and a fast activating, transient type, voltage-gated potassi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2001
2001
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 36 publications
1
6
1
Order By: Relevance
“…The effects of all-trans retinoic acid show that our in-vitro model recapitulates responses observed in primary tissue from the vertebrate inner ear (Kelley et al, 1993;Raz & Kelley, 1999;Sokolowski et al, 1999). We show that retinoic acid upregulates expression of myosin VIIa and enhances expression of potassium conductances similar to those observed in native hair cells.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The effects of all-trans retinoic acid show that our in-vitro model recapitulates responses observed in primary tissue from the vertebrate inner ear (Kelley et al, 1993;Raz & Kelley, 1999;Sokolowski et al, 1999). We show that retinoic acid upregulates expression of myosin VIIa and enhances expression of potassium conductances similar to those observed in native hair cells.…”
Section: Discussionsupporting
confidence: 80%
“…I K,late was expressed only in cells cultured in serum and was not activated by retinoic acid. Despite this, retinoic acid enhanced current density as predicted from studies on its effects on developing chick inner ear in vitro, where it enhanced hair cell differentiation and the expression of voltage-gated potassium currents (Sokolowski et al, 1999). These effects are probably indirect as we found no evidence for activation of specific ion channel subunits in VOT-E36.…”
Section: Membrane Conductances In Vot-e36contrasting
confidence: 40%
See 1 more Smart Citation
“…Recently, Winston et al (37) reported an upregualtion of VR-1 mRNA in dorsal root ganglion neurons cultured in the presence of NGF. Others have reported changes in the expression of both ligand-and voltage-gated ion channels (8,34), which will also affect the functional properties of afferent neurons and alter their firing patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Once the cochlea was removed as described above, the tegmentum vasculosum was cut away with iridectomy scissors. As described previously (Sokolowski et al,1999), the cochlea was placed in a low‐calcium saline containing protease XXIV (0.09 mg/ml) (Sigma, St. Louis, MO), and the tectorial membrane was removed with forceps after 2–4 min. The cochlea was rinsed in normal divalent saline and tissue was fixed and embedded as described previously (Sokolowski and Cunningham,1996).…”
Section: Methodsmentioning
confidence: 99%